2020
DOI: 10.1080/20008198.2020.1777809
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and potential effectiveness of an intensive trauma-focused treatment programme for families with PTSD and mild intellectual disability

Abstract: Background: Persons with mild intellectual disabilities or borderline intellectual functioning (MID-BIF; IQ 50-85) have a higher risk of being exposed to traumatic events and developing posttraumatic stress disorder (PTSD). EMDR therapy has shown to be applicable, safe and potentially effective for the treatment of PTSD in individuals with MID-BIF. However, in traumatized multi-problem families with MID-BIF and (impending) out of home placement of children, standard PTSD treatment in an outpatient setting may … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…This is in sharp contrast with regular outpatient traumafocused treatment programmes (Ragsdale et al, 2020;ranging from 30% to 62%). The high retention level may be due to the condensed format of frequently scheduled sessions conducted within a shorter time frame (Mevissen et al, 2020;Ragsdale et al, 2020;Sciarrino et al, 2020;Silverstone et al, 2016), the clear view and perspective as to when treatment ends and the fact that the patients stayed in the clinic during the treatment days (van Woudenberg et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in sharp contrast with regular outpatient traumafocused treatment programmes (Ragsdale et al, 2020;ranging from 30% to 62%). The high retention level may be due to the condensed format of frequently scheduled sessions conducted within a shorter time frame (Mevissen et al, 2020;Ragsdale et al, 2020;Sciarrino et al, 2020;Silverstone et al, 2016), the clear view and perspective as to when treatment ends and the fact that the patients stayed in the clinic during the treatment days (van Woudenberg et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence, a significant number of patients ultimately do not receive treatment they could benefit from. There is evidence suggesting that retention in treatment decreases when treatment is intensified: that is, applying a higher frequency of therapy sessions within a shorter time frame (Mevissen, Ooms-Evers, Serra, de Jongh, & Didden, 2020;Ragsdale, Watkins, Sherrill, Zwiebach, & Rothbaum, 2020;Sciarrino, Warnecke, & Teng, 2020;Silverstone, Greenspan, Silverstone, Sawa, & Linder, 2016). For instance, Hendriks et al (2017) and her colleagues developed an intensive PE therapy programme and explored the effectiveness of this programme in 10 adolescent patients with severe PTSD and comorbid disorders following multiple interpersonal trauma.…”
Section: Introductionmentioning
confidence: 99%
“…Of the seven studies that assessed efficacy, reductions in post-traumatic symptomatology, general psychiatric challenges, behavioural difficulties and daily life impairment were reported. Two studies reported improved parent outcomes (Harley et al, 2014;Mevissen et al, 2020); however, in one study, scores on the majority of parental stress subscales remained elevated post intervention (Harley et al, 2014). Of note, the results of one study indicated that their TF-CBT intervention was largely ineffective in reducing internalising and externalising problems in children; however, aggressive behaviour and rule-breaking did decrease (Holstead & Dalton, 2013).…”
Section: Findings Of Studies That Evaluated Efficacymentioning
confidence: 94%
“…Eight of the studies that implemented a therapeutic support used nonverbal, sensory, and/or play-based therapeutic techniques (Guest & Ohrt, 2018;Harley et al, 2014;Horovitz, 1981;Kildahl et al, 2021;Mevissen et al, 2011Mevissen et al, , 2017Mevissen et al, , 2020Mohamed & Mkabile, 2015), and an additional study made an explicit attempt to integrate their participant's interests and preferred activities into the intervention process (Gerhardt & Smith, 2020). Efforts to modify language and match the communication abilities of participants were reported across five studies, which included the provision of clear instructions (Mevissen et al, 2011(Mevissen et al, , 2017(Mevissen et al, , 2020, simplified communication (Guest & Ohrt, 2018;Ooms-Evers et al, 2021), and the use of positive language (Harley et al, 2014). A further study emphasised the importance of reinforcing and validating verbal communication attempts (Kildahl et al, 2021).…”
Section: Methods Of Deliverymentioning
confidence: 99%
See 1 more Smart Citation